Intergenerational Mobility and Income Effects for Entrepreneurial Activity in Mexico - Viviana Velez-Grajales; Roberto Velez-Grajales (Inter-American Development Bank (IDB), 2012)
This paper uses the Mexican Social Mobility Survey 2006 to analyze intergenerational social mobility as it relates to entrepreneurial activity. First, the paper analyzes whether entrepreneurs experience greater upward social mobility than self-employed workers or employees. Second, probit models are estimated to identify whether predetermined characteristics are the main determinants of the decision to become an entrepreneur. Third, using the propensity score matching method (PSM), the paper estimates the effect of entrepreneurial activity on income. Results show that entrepreneurs have more options for upward social mobility. For entrepreneurs with low-income parents, it is more difficult to reach the top of the socioeconomic distribution compared to those with middle- or upper-class parents. Second, the probability of becoming an entrepreneur increases when the respondents father was an entrepreneur. Finally, the mean effect of entrepreneurial activity on income is positive, and is greater for those whose parents belonged to the extreme ends of the socioeconomic distribution.
Keywords: C21; J62; L26; 330